Is there a dark side of Big Data-point, counterpoint - Tore Håkonsson; Tim Carroll (Journal of Organization Design, 2016)
Haakonsson and Carroll see two sides to Big Data. In his executive experience, Haakansson finds big data slows the decision making process and the implementation of decisions as well. Executives tend to wait for more data just because it is there. Is there a solution? Haakonsson argues that leadership based upon experience and courage is needed. Carroll sees a different world where we have continually improved tools which can automate the analyses of big data and give us answers quickly. That is, big data is not a problem, but a solution for executives. But there is also a problem; what are the right questions to ask? Without hypotheses, the questions are endless. Leaders must utilize their experience, intuition and insights to ask the right questions - not all the possible questions which big data can address. Is there a synthesis? Big data by itself is not necessarily a good thing; but it can be if leaders have the courage to move on in a timely manner where they ask the right questions - not all the questions possible that big data can address.
Keywords: 650